Tingkat Daya Serap Siswa Terhadap Pendidikan Agama Islam Pada Sekolah Menengah Pertama - Bahrus Surur Subhan Adi Santoso (Jurnal Pendidikan Islam, 2021)
Good student absorption of Islamic religious education can be a benchmark for successful implementation and learning of Islamic religious education in schools. The level of student absorption of Islamic religious education can be continuously improved in various ways. In learning to increase absorption, students can apply various methods accompanied by the use of learning media. In addition to the application of learning methods or media, student absorption can be increased by continuously increasing the supporting factors and minimizing the inhibiting factors that can affect student absorption of Islamic religious education. This success cannot be separated from the influence of supporting factors, namely a conducive classroom atmosphere or school environment, physical health, proper student seating layout, high intelligence and high motivation in participating in teaching and learning activities. In addition to supporting factors, it is necessary to know the factors that can be an obstacle to student absorption of Islamic religious education in junior high schools, namely: declining health so that it has an impact on decreasing intelligence and learning motivation and ultimately causes a learning environment that is not conducive.